The Effect of the swnR Gene on Swainsonine Biosynthesis in Alternaria oxytropis OW7.8, an Endophytic Fungus of Oxytropis glabra - Ning Ding; Chang Liu; Ping Lu; Lu Bai; Bo Yuan (Microorganisms)
The swnR gene was cloned in the endophytic fungus Alternaria oxytropis OW 7.8 isolated from Oxytropis glabra, and the gene knockout mutant ΔswnR was first constructed in this study. Compared with A. oxytropis OW 7.8, the ΔswnR exhibited distinct morphological alterations in both colony and mycelial structure, a slower growth rate, and significant reductions in swainsonine (SW) levels, indicating that the function of the swnR gene promoted SW biosynthesis. Six differentially expressed genes (DEGs) closely associated with SW synthesis were identified by transcriptomic analysis of A. oxytropis OW 7.8 and ΔswnR, with P5CR, swnR, swnK, swnH2, and swnH1 downregulating, and sac upregulating. The expression levels of the six genes were consistent with the transcriptomic analysis results. Five differential metabolites (DEMs) closely associated with SW synthesis were identified by metabolomic analysis, with L-Lys, L-Glutamic acid, Saccharopine, and L-Proline upregulating, and L-PA downregulating. The results lay the foundation for the in-depth elucidation of molecular mechanisms and SW synthesis pathways in fungi, and are also of importance for the prevention of locoism in livestock, the control and utilization of locoweeds, and the protection and sustainable development of grassland ecosystems.